Evidence-based support for integration of Quality Declared Seeds (QDS) in Uganda's new seed policy, with 2,000 farmers already trained in the production of QDS - CGIAR Research Program on Policies, Institutions, and Markets (2020)
As recommended by a PIM study, Uganda's new seed policy introduces Quality Declared Seeds (QDS) - a new seed class produced by registered farmers and community seed banks with less costly provisions for quality assurance, allowing farmers to commercialize popular varieties at the local level and thus improving access to quality seeds. Two community seedbanks are already QDS certified and five have started the certification process. 2,000 participant farmers were trained in the production of QDS in 2020,